2012
DOI: 10.3892/ol.2012.932
|View full text |Cite
|
Sign up to set email alerts
|

Urotensin II contributes to the formation of lung adenocarcinoma inflammatory microenvironment through the NF-κB pathway in tumor-bearing nude mice

Abstract: Abstract. Urotensin II (UII), a somatostatin-like cyclic peptide, was originally isolated from the fish urophysis. Our previous study showed that UII stimulates the proliferation of A549 lung adenocarcinoma cells and promotes tumor growth in a nude mouse xenograft model, suggesting that UII may contribute to the pathogenesis of lung adenocarcinoma. In this study, the underlying mechanism for UII to promote lung adenocarcinoma growth was explored by observing the effect of UII on the tumor inflammatory microenv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…Both UT mRNA and UT protein are present in human lung adenocarcinoma A549 cells and exogenous UII activates proliferation of these cells in vitro and in vivo (Wu et al, 2010). UII-evoked lung adenocarcinoma growth is likely mediated through the nuclear factor kB pathway (Zhou et al, 2012). Abundant expression of UT mRNA and UT protein is observed in the interstitial nodular lesions of patients with lymphangioleiomyomatosis, whereas UT mRNA is not expressed in normal human lungs (Kristof et al, 2010).…”
Section: G Urotensin II Receptor In Tumor Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both UT mRNA and UT protein are present in human lung adenocarcinoma A549 cells and exogenous UII activates proliferation of these cells in vitro and in vivo (Wu et al, 2010). UII-evoked lung adenocarcinoma growth is likely mediated through the nuclear factor kB pathway (Zhou et al, 2012). Abundant expression of UT mRNA and UT protein is observed in the interstitial nodular lesions of patients with lymphangioleiomyomatosis, whereas UT mRNA is not expressed in normal human lungs (Kristof et al, 2010).…”
Section: G Urotensin II Receptor In Tumor Cellsmentioning
confidence: 99%
“…Immunoreactive UII and URP are present in interstitial nodular lesions of lungs from patients with lymphangioleiomyomatosis, a rare disease characterized by abnormal proliferation of smooth muscle-like cells in the pulmonary interstitium (Kristof et al, 2010). UII promotes lung adenocarcinoma growth via a mechanism involving activation of the nuclear factor kB pathway and a proinflammatory microenvironment (Zhou et al, 2012).…”
Section: Urotensin II and Urotensin Ii-related Peptide In Tumor Cellsmentioning
confidence: 99%
“…It is well known that NF-jB in mammals plays a critical role in the activation of immune cells by upregulating the expression of many cytokines (e.g., IL-1, IL-2, IL-6, IL-12, TNF-a, IFN-c, and GM-CSF) essential to the immune response (Liang et al, 2013). UII increased the phosphorylation of NF-jB in lung adenocarcinoma A549 cells and induced the upregulation of cytokines such as IL-6 and TNFa (Zhou et al, 2012). Furthermore, the mutation of NF-jB binding sites on the IL-8 promoter reduced promoter activity in human umbilical vein endothelial cells, suggesting that the NF-jB transcription factor plays key roles in the induction of IL-8 expression (Lee et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…UII is a somatostatin-like cyclic undecapeptide that has been identified as a potent mammalian vasoconstrictor (15). As well as affecting vascular tone, UII stimulates cell proliferation, and previous studies have indicated that is involved in the pathogenesis of certain tumors, including breast, bladder, colon and prostate cancer (1214,28). Our previous study demonstrated that the expression of the UII/UT system was increased in HCC tissues and cell lines, and that exogenous administration of UII regulated the proliferation of cancer cells and increased the expression of various transcription factors, including ERK, PKC and p38 MAPK (18,20).…”
Section: Discussionmentioning
confidence: 99%